2010
DOI: 10.1111/j.1745-7599.2010.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative fever: A normal inflammatory response or cause for concern

Abstract: The role of the APRN in managing surgical patients requires being able to accurately assess and evaluate the cause of postoperative fever and take action accordingly. That means taking into account a variety of factors (e.g., patient's medical history, physical examination findings, and type of surgery), so that appropriate diagnostic tests can be ordered to evaluate the cause of the postoperative fever. By being aware of the causes of postoperative fever, the APRN can also take prophylactic action to decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Changes of the leukocytes count were proportional to the changes of the neutrophils count. Numerous studies have shown that elevated body temperature is a frequent sign of the first and second postoperative day in large operative procedures, mostly caused by an inflammatory stimulus of surgery ( 11 , 12 , 13 ). Wortel et al ( 14 ) reported that the postoperative level of IL-6 is directly proportional to the value body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Changes of the leukocytes count were proportional to the changes of the neutrophils count. Numerous studies have shown that elevated body temperature is a frequent sign of the first and second postoperative day in large operative procedures, mostly caused by an inflammatory stimulus of surgery ( 11 , 12 , 13 ). Wortel et al ( 14 ) reported that the postoperative level of IL-6 is directly proportional to the value body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, occurrence of postoperative fever does not seem to be related to a worse outcome, which has also been reported in a prospective trial enrolling 2,311 immune suppressed patients with colorectal cancer [18]. If confirmed in other trials, the demand for excessive work-up in patients with early postoperative fever, unless there are additional clinical symptoms and particular comorbidities such as neutropenia, remains questionable [2,4].…”
Section: Discussionmentioning
confidence: 87%
“…Although the association of fever and recent surgery is well known, fever persisting after the third postoperative day is often a concern to surgeons and nurses and leads to further investigation [1][2][3][4]. When an infection is suspected following orthopaedic implant surgery many patients presumably receive antibiotic therapy without clear reason [2,5] or perioperative prophylaxis is prolonged beyond one day in exceptional situations [6], all with potential adverse effects of unnecessary therapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…The most acceptable conclusion was that fever was the physiological response due to the damage caused by surgical trauma, and the degree of fever was correlated with the extent of tissue trauma during surgery [4,8,11,13]. The in ammation reaction stimulated by tissue trauma could trigger the release of cytokines such as IL1, IL6 and TNF-a in the local surgical area, and the released cytokines acted as endogenous pyrogens to stimulate the preoptic area of the hypothalamus to increase prostaglandin production, raising the thermoregulatory set point for body temperature [9,13,14,19,20]. Based on these theories, we proposed that when the drainage tube was removed, the local in ammatory cytokines could not ow out, and then a small hematoma formed.…”
Section: Discussionmentioning
confidence: 99%